Spin-wave propagation in α-Fe2O3 nanorods: the effect of confinement and disorder. (7th March 2019) - Cortie, David; Casillas-Garcia, Gilberto; Squires, Andrew; Mole, Richard; Wang, Xiaolin; Liu, Yun; Chen, Yen-Hua; Yu, Dehong
Abstract: Spin-wave excitations in α -Fe2 O3 nanorods were directly detected using time-of-flight inelastic neutron spectroscopy. The dispersive magnon features are compared with those in bulk α -Fe2 O3 particles at various temperatures to highlight differences in mode intensity and width. The interchanged spectral intensities in the nanorod are a consequence of a suppressed spin orientation, and this is also evident in the neutron diffraction which demonstates that the weak ferromagnetic phase survives to 1.5 K. Transmission electron microscopy shows that the ellipsoidal particles are single-crystalline with a typical length of 300 ± 100 nm and diameter of 60 ± 10 nm. The main magnon features are similar in bulk and nanoforms and can be explained using a model Hamiltonian based on Samuelson and Shirane's classical theory with exchange constants of J 1 = −1.03 meV, J 2 = −0.28 meV, J 3 = 5.12 meV and J 4 = 4.00 meV. Numerical simulations show that two distinct mechanisms may contribute to the magnon line broadening in the nanorods: a distribution of exchange interactions caused by disorder, and a shortened quasiparticle lifetime caused by the scattering of spin waves at surfaces.